Project: Heuristic-Functional Animated Movie The Boy’s Dream (Number of the First Tenner) - HILČENKO, Slavojlub; MEDIĆ, Branko (Journal of Education, Technology and Computer Science, 2015)
Animated movie The Boy’s Dream (number of the first tenner), is the latestproject of our instructional team that complies with the latest international requirementsin order to develop a e-tutoring platform. In addition, especially inaccordance to the needs and possibilities of Generations „Z”, and on the otherhand the concept of heuristic algorithms stimulates intuition and common sensein children. Furthermore, the targeted group – children of preschool institutionsengaged in monitoring and resolving application, the platform requires and developstheir functional-logical potential. The project includes an interactive quizwith 12-manipulation tasks, like upgrading animated themes (and on the otherhand, generates a report on the performance and their abilities (average scores ofthe individual, the group and the percentage of correct answers on questions)which will help teachers to better recognize the level of knowledge on this areaand problematic places of learning) as well as the methodological manual. Theaim of the paper is to present the project for its full implementation we suggesta period of 2 years.